PENGARUH TEMPORARY AND PERMANENT DIFFERENCE TERHADAP PERTUMBUHAN LABA DENGAN SMALL AND LARGE BOOK TAX DIFFERENCE SEBAGAI VARIABEL MODERATING - Uswatun Khasanah; Nur Diana; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
The purpose of this research is to determine the effect of temporary and permanent difference on earnings growth with small and large book tax difference as a moderating variable. The independent variable in this research is temporary and permanent difference, while the dependent variable is profit growth and small and large book tax difference as the moderating variable. This type of research is correlational research with a quantitative approach because the data used are in the form of numbers and numbers. The data source in this research is secondary data in the form of annual report with the data collection method in the form of documentation. The population in this study is the banks that have been listed on the Indonesia Stock Exchange for the period 2015-2018. This study used 31 samples of banks that have selected through purposive sampling for three year. Hypotheses were tested using descriptive statistical analysis, normality tests, classic assumption tests, multiple linear regression with moderating variables, and hypothesis testing using SPSS version 14. The results showed that the temporary difference variable positively and significantly affected earnings growth (0.015 < 0.05). While the permanent difference variable does not affect profit growth (0.599> 0.05). The small and large book tax difference variable also has no significant effect on the relationship between temporary and permanent difference on profit growth.Keywords: Temporary Difference, Permanent Difference, Profit Growth and small and large book tax difference.